STUDI KOMPARATIF HASIL BELAJAR KOGNITIF KEWIRAUSAHAAN MELALUI PENERAPAN MODEL PEMBELAJARAN TALKING STICK DAN SNOWBALL THROWING PADA SISWA KELAS X SMK KRISTEN 1 SURAKARTA TAHUN PELAJARAN 2015/2016 - Dowes Ardi Nugroho; Harini Harini; Sunarto Sunarto (Department of Economics Education, Universitas Sebelas Maret, 2018)
This study was conducted to find out whether there’s a different in students’ entrepreneurship learning outcome through 2 different study model, talking stick and snowball throwing study model.A quantitative experimental study was conducted to all of 10th grader in SMK Kristen 1 Surakarta. Chosen subjects were taken through cluster sampling methods and came from Accounting and Office Administration 10th grader. 21 subjects in 10th grade Accounting were taught with talking stick study model and 32 subjects in 10th grade Office Administration were taught with snowball throwing study model. Data collection techniques in this study is documentation and a written test. The data in this study was analyzed using Independent Samples Test technique with 5% signification. Normality and homogeneity test were done using SPSS 21.According to study and analytical data result, it can be concluded that there’s a difference in entrepreneurship learning outcomes between subjects taught with talking stick and snowball throwing study model (Fcounted = 10,687 > Ftable2,007584) at 5% level of significant.